The Impact of Organizational Learning Capability on Product Innovation Performance: Evidence from the Turkish Manufacturing Sector - Özlem Yaşar Uğurlu; Mustafa Kurt (Emerging Markets Journal, 2016)
This study aims to examine the effect of organizational learning capability on product innovation performance in the manufacturing sector using empirical data. A survey was conducted with 120 firms that were on the list of Top 1000 Firms of Turkey and registered with the Istanbul Chamber of Industry, to examine the relationship between the dimensions of organizational learning capability and the dimensions of product innovation performance. The findings of the study indicate a positive relationship between organizational learning capability and product innovation performance.